Analysis Of Nahwu Learning Difficulties In Students Of Class VIII Syamsul Ulum Boarding School Bandung - Malik, Stevan; Hudaya, Ujang (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2022)
Learning Qawaid, especially Nahwu at school, has various problems. The factors that cause the problem are both internal and external. The purposes of this study were 1) to find out the factors of difficulty learning Nahwu about Kalam in class VIII students of the Syamsul Ulum Islamic Boarding School Ujung Berung Bandung, and 2) to find out the solution to the difficulties in learning Nahwu about Kalam in class VIII Syamsul Islamic Boarding School students at Ujung Berung Bandung. The data of this study were through tests and non-tests. The test data collection tool used is in the form of test questions given to students—non-test data tools used in questionnaires, observations, and interviews. The conclusions of this study are: 1) The factors that cause student difficulties that come from themselves are 22.04%, factors that come from the family environment are 30%, factors that come from the school environment are 35.44%, and the last factor comes from from the school environment. Community environment by 12.52% 2) The solutions offered by researchers to research results include: a) Self: more focused on understanding the explanation of the material given by the teacher in class, study habits pay more attention; b) Family Environment: problems in the family must be resolved by deliberation with fellow family members; c) School environment: more expanded and updated media facilities, learning tools, book collections or teaching materials; d) Community environment: voting in association, time management in studying and working including organization.